Utilizing Instagram Media For Digital Marketing In The 2021 Yogyakarta Cultural Festival - Noorfitri Rizky Dwiyani; Lintang Hitasukha; Muhammad Abdurrahman Haikal; Salwa Yunaika Adani (TUMATA: Journal of Arts and Cultural Management, 2023)
Festival Kesenian Yogyakarta (FKY) is an annual cultural art event in Yogyakarta. FKY was first held in 1989 with the concept of the people's market. Starting in 2019, it further expanded its focus on the realm of cultural life in Yogyakarta with the courage to change the name of the Festival Kesenian Yogyakarta to the Festival Kebudayaan Yogyakarta (Yogyakarta Cultural Festival). The purpose of this research is to describe Utilizing Instagram Media For Digital Marketing In The 2021 Yogyakarta Cultural Festival. This research uses a qualitative method through a case study with a marketing approach and uses the 4P+3P marketing mix elements, namely product, price, promotion, channel, distribution/place, people, process, and physical evidence. Data obtained by interview, observation, documentation and the results of this study indicate that the marketing carried out by the 2021 FKY committee through the marketing mix has a positive impact on sales and wider reach to the creative industry for 2021 FKY. The most influential elements are product, price, promotion, and process. The elements that have not been maximized are places and people. Human resource management is the main obstacle in the process from beginning to end in the 2021 FKY. The conclusions obtained from the research show that the Sambatan program applies the 7p marketing mix elements in the implementation of the marketing process, although the elements have not been maximized and need improvement.